Induction and early identification of tetraploid black locust by hypocotyl in vitro - Li, Xiuyu; Zhang, Zijie; Ren, Yunhui; Feng, Yue; Guo, Qi; Dong, Li; Sun, Yuhan; Li, Yun (In vitro cellular & developmental biology. Plant, 2021)
Tetraploid black locust (Robinia pseudoacacia L.) has advantages over diploid varieties in growth and stress resistance. Previous studies had shown that tetraploid black locust can be induced only by treating shoot tips of the germinating seeds with colchicine. In order to establish a simpler and more efficient tetraploid induction method in black locust, we induced tetraploid plants by treating the hypocotyls from in vitro-gvown seedlings with different concentrations of colchicine, and then provided a method for tetraploid identification based on stomatal size and density in this study. The highest induction efficiency was 53.33% by treating hypocotyl expiants with 70 mg-L⁻¹ colchicine for 2 d. Tetraploid black locust was significantly different from diploid in morphological characteristics. Leaf area, leaf thickness, chlorophyll content, stomatal length, and stomatal width were greater in tetraploid plants than in diploid plants, whereas the opposite was true for leaf aspect ratio, stomatal index, and stomatal density. The differences in stomatal size and density between diploid and tetraploid were nearly two times; therefore, size and density of stomata can be used as a stable and distinct marker to rapidly screen tetraploids. The results of this study suggested that the hypocotyl was an ideal material to induce tetraploid black locust in vitro and confirmed that stomatal size and density could be an effective and reliable marker to identify ploidy level in black locust.